In vitro Trypanocidal Activity, Genomic Analysis of Isolates, and in vivo Transcription of Type VI Secretion System of Serratia marcescens Belonging to the Microbiota of Rhodnius prolixus Digestive Tract - da Mota, Fabio Faria; Castro, Daniele Pereira; Vieira, Cecilia Stahl; Gumiel, Marcia; de Albuquerque, Julia Peixoto; Carels, Nicolas; Azambuja, Patricia (Frontiers in Microbiology, 2019)
Serratia marcescens is a bacterium with the ability to colonize several niches, including some eukaryotic hosts. S. marcescens have been recently found in the gut of hematophagous insects that act as vectors of parasites, such as Anopheles, Rhodnius, and Triatoma. While some S. marcescens strains have been reported as symbiotic or pathogenic to other insects, the role of S. marcescens populations from gut microbiota of Rhodnius prolixus, insect vector of Chagas' disease, remains unknown. Bacterial colonies from R. prolixus gut were isolated on BHI agar. After BOX-PCR fingerprinting, the genomic sequences of two isolates RPA1 and RPH1 were compared to others S. marcescens from NCBI database in other to estimate their evolutionary divergence. Trypanolytic activity in vitro of these two bacterial isolates against two Trypanosoma cruzi DM28c clone and Y strain was assessed by microscopy. In addition, in vivo detection of type VI secretion system (T6SS) gene expression was observed by RT-PCR. Comparative genomics of S. marcescens RPA1 and RPH1 reveals, besides plasmid presence and genomic islands, genes related to motility, attachment and quorum-sensing in both genomes while genes for urea hydrolysis and Type II secretion system were found only in RPA1 genome. In vitro trypanolytic activity of both S. marcescens strains was stronger in their stationary phases of growth than in their exponential ones. In this way, 65-70% and 85-90% of epimastigotes (Dm28c clone and Y strain, respectively) were lysed after incubation with RPA1 or RPH1 in stationary phase. Although in vivo T6SS transcripts have been observed up to 40 days after feeding with T. cruzi infected blood, neither morbidity nor mortality was observed in R. prolixus. In this report, we made available two trypanolytic S. marcescens strains from R. prolixus gut to the scientific community together with their genomic sequences. We described genomic features with the purpose of bringing new insights into the S. marcescens adaptations for colonization of the specific niche of triatomine guts. This study provides the basis for a better understanding of the role of S. marcescens in the microbiota of R. prolixus gut as a potential antagonist of T. cruzi in this complex system.